2011
DOI: 10.1080/09583157.2011.632077
|View full text |Cite
|
Sign up to set email alerts
|

Artificial diets for rearing the coconut hispine beetle,Brontispa longissima(Coleoptera: Chrysomelidae), and their suitability to two specialist parasitoids

Abstract: The coconut hispine beetle, Brontispa longissima (Gestro), is a serious invasive pest that infests young unopened fronds of coconut palms (Cocos nucifera L.) in Southeast Asia. We previously developed the first artificial diet for rearing B. longissima larvae, which contained a leaf powder of young coconut fronds. Because the fronds are required for healthy growth of coconut palms, it is necessary to reduce their use for rearing the beetles. In this study, we tested two new artificial diets for the beetle larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
(14 reference statements)
1
7
1
Order By: Relevance
“…In the present experiment, the proportion of sixth-instar larvae with Diet C was lower than with the control diet. These indicate that Diet C is less optimal than fresh coconut leaves as food for B. longissima, but Diet C nonetheless enhanced the survival rate compared with the other diets in this study (Table 2) and with our previous diets ( Table 2; Ichiki et al 2009Ichiki et al , 2011.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…In the present experiment, the proportion of sixth-instar larvae with Diet C was lower than with the control diet. These indicate that Diet C is less optimal than fresh coconut leaves as food for B. longissima, but Diet C nonetheless enhanced the survival rate compared with the other diets in this study (Table 2) and with our previous diets ( Table 2; Ichiki et al 2009Ichiki et al , 2011.…”
Section: Discussioncontrasting
confidence: 57%
“…The artiÞcial diets were prepared by modifying the diet reported by Ichiki et al (2009). Ichiki et al (2011) developed two artiÞcial diets made from mature coconut leaf powder and orchard grass powder as the main ingredients, but the survival rates of beetles that were fed these diets were lower than those that were fed the diet made from young coconut leaf powder reported by Ichiki et al (2009). Therefore, we used the diet developed by Ichiki et al (2009) as the control in the current study.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…More convenient plants will be needed for mass rearing of B. hngissima. Ichiki et al (2009) reported an artificial diet containing dried coconut leaf powder for B. hngissima, and 40% of larvae reared on the artificial diet grew to the adult stage. However, if continuously reared on this artificial diet, the adults did not lay fertile eggs.…”
mentioning
confidence: 99%